The engineered biphenyl dioxygenases enhanced the metabolism of dibenzofuran. (July 2021) - Wang, Yuan; Sun, Chengcheng; Min, Jun; Li, Bingjun; Li, Junde; Chen, Weiwei; Kong, Yachao; Hu, Xiaoke
Abstract: As a model compound of dioxin, dibenzofuran is a persistent environmental pollutant. Several investigations have provided evidence that biphenyl dioxygenase (BPDO) from Burkholderia xenovorans LB400 could be engineered to further enhance the metabolite profile of biphenyl and polychlorinated biphenyl through lateral oxygenation. In this context, we examined the ability of the evolved BphAES283M, BphAEp4-S283M and BphAERR41-S283M to transform dibenzofuran with features of co-planar and ortho -substituted biphenyls. For BphAES283M, BphAEp4-S283M and BphAERR41-S283M, the k cat / K m value toward dibenzofuran was 4.5 times, 3 times and 2.5 times higher than that of the wild-type enzyme, respectively. Meanwhile, biochemical experiments determined that the substitution Ser283Met affected the regiospecificity of product formation, and the primary metabolite produced by BphAES283M was identified as 3, 4-dihydro-3, 4-dihydroxy-dibenzofuran. The structural analysis revealed residue Met283 as critical to generate a flexible catalytic cavity and a productive orientation of dibenzofuran during the catalytic reaction. Collectively, this study provides the theoretical basis and technical support for the significant development of better promising biocatalysts to effectively degrade dibenzofuran and other aromatic pollutants in the environment. Highlights: BphAES283M, BphAEp4-S283M and BphAERR41-S283M variants were applied for dibenzofuran degradation. The Ser283Met substitution significantly enhanced the catalytic efficiency of BphAELB400 toward dibenzofuran. The Ser283Met substitution influenced the regiospecificity of BphAELB400 toward dibenzofuran. Docking analysis indicated the orientation of dibenzofuran had altered in enzyme-substrate binding.